Cultural and Biochemical Characterization of Staphylococcus aureus Isolates from Bovine Clinical and Subclinical Mastitis - Maddela, Pallavi; Makwana, Pushpa M; Parmar, Saurabh M; Kalyani, Irsadullahkhan H; Patel, Dharmesh R; Parasana, Dixit K (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Bovine mastitis causes huge economic losses to the dairy industry all over the world. Staphylococcus aureus is a most common causative agent of bovine mastitis. The study was undertaken with an objective of isolation, identification and biochemical characterization of Staphylococcus aureus isolated from bovine mastitis cases. Total of 256 bovine milk samples (32 from clinical mastitis and 224 from suspected cases of subclinical mastitis) were collected from in and around Navsari. Of the 224 SCM suspected milk samples screened by California mastitis test (CMT), 108 (48.21 %) samples were found positive for subclinical mastitis, whereas all 32 clinical mastitis samples were CMT positive. Thus total 140 bovine milk samples (32 clinical and 108 subclinical mastitis) were used for detection of Staphylococcus aureus. Out of these, 17 (12.14%) isolates were identified as Staphylococcus aureus on the basis of cultural characteristics and biochemical tests. From 17 S. aureus, 16 (94.11%) isolates were categorized as mannitol fermenter and coagulase positive, while 1 (5.88%) isolate was mannitol non-fermenter and coagulase negative. Majority of the isolates 10 (58.82%) exhibited beta-haemolysis, whereas 5 (29.41%) isolates showed alpha-haemolysis and 2 (11.76%) isolates were non-haemolytic on 5% sheep blood agar. Among 17 S. aureus isolates, 14 (82.35%) isolates exhibited slime production, while 6 (11.76%) isolates were negative for slime production. This study showed overall 12.14 % incidence of bovine mastitis by Staphylococcus aureus, whereas cases of clinical mastitis and sub-clinical mastitis noted as 9.30% and 12.96%, respectively, by S. aureus.